The Influence of Intellectual Capital, Islamic Corporate Social Responsibility and Islamic Corporate Governance on the Value of Companies in Islamic Banks - Ahmad; Muntu Abdullah; Fitriaman (Takaza Innovatix Labs Ltd., 2024)
This study aims to find out and analyze the influence of Intellectual Capital, Islamic Corporate Social Responsibility, and Islamic Corporate Governance on the value of companies in Sharia Commercial Banks registered with the Financial Services Authority (OJK) during the 2021-2024 period. This study uses a quantitative approach with a secondary type of data in the form of annual financial reports obtained from the official website of each company. The sample determination technique used the purposive sampling method, so that 9 Sharia Commercial Banks were obtained with a total of 36 observations during the research period. The independent variables in this study are Intellectual Capital, Islamic Corporate Social Responsibility, and Islamic Corporate Governance, while the dependent variables are the value of the company proxied with Economic Value Added (EVA). The data analysis method used was multiple linear regression analysis with the help of IBM SPSS Statistics 26. The results of the study show that Intellectual Capital and Islamic Corporate Social Responsibility have a positive and significant effect on company value, while Islamic Corporate Governance does not have a significant effect on company value. The conclusion of this study indicates that Intellectual Capital and Islamic Corporate Social Responsibility were able to significantly increase the value of the company in the study period, while Islamic Corporate Governance was not able to have a significant influence on the value of the company